2011
DOI: 10.3390/molecules16032146
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Natural Products

Abstract: Malaria is a human infectious disease that is caused by four species of Plasmodium. It is responsible for more than 1 million deaths per year. Natural products contain a great variety of chemical structures and have been screened for antiplasmodial activity as potential sources of new antimalarial drugs. This review highlights studies on natural products with antimalarial and antiplasmodial activity reported in the literature from January 2009 to November 2010. A total of 360 antiplasmodial natural products co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 111 publications
(127 reference statements)
1
63
1
1
Order By: Relevance
“…Flavonoids comprising a large group of polyphenolic secondary metabolites possess antimalarial activities. Triterpenoids including saponins have been found to be active on P. falciparum [3]. The observed antimalarial activity of water extract might also be attributed to the presence of anthraquinones which were absent in the methanol extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids comprising a large group of polyphenolic secondary metabolites possess antimalarial activities. Triterpenoids including saponins have been found to be active on P. falciparum [3]. The observed antimalarial activity of water extract might also be attributed to the presence of anthraquinones which were absent in the methanol extract.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the recognition of the global importance of fighting against malaria, efforts to discover and develop new antimalarials from plant sources has increased [3].…”
Section: Introductionmentioning
confidence: 99%
“…4 Many others have also been described as active in vitro against the parasite and could become lead compounds with new mechanisms of action in order to overcome resistance. 5 Triterpene-rich plant extracts containing betulinic acid (2a, Figure 2) have been reported as antiplasmodial. Initial evidences of the activity of betulinic acid indicated a moderately action against P. falciparum (NF 54) with IC 50 values (concentration in that the growth of the parasites is 50% inhibited) = 10.5 µg mL -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The history of malaria has shown that plants are a source of new molecules. This is the case of quinine that has been isolated from Chincona and artemisinin that has been isolated from Artemisia annua (Batista et al, 2009;Bero and Joëlle, 2011;Bero et al, 2009;Kaur et al, 2009;Nogueira and Lopes, 2011;Phillipson and Wright, 1991). Over 80% of the world's population use medicinal plants for healing (WHO, 2008(WHO, , 2010.…”
Section: Introductionmentioning
confidence: 99%